Laparoscopic management in an adult patient with intestinal obstruction secondary to congenital midgut malrotation: a case report and review of the literature - Mares, Asya Zubillaga; Nuñez-Venzor, Alejandra; Chávez-Hernandez, Fátima; Barlandas-Quintana, Erika; Lopez-Godinez, Maria Fernanda (International Surgery Journal, 2022)
Intestinal malrotation is the failure of the fetal intestine to complete a 270-degree counter clockwise rotation around the superior mesenteric artery, resulting in positional and fixation abnormalities of the small and large intestine. Adult presentation is uncommon with an estimated incidence of 0.2 to 0.5%. There is no consensus on treatment in patients with asymptomatic intestinal malrotation in adults. The aim of this document was to report and review a case of intestinal malrotation conditioning intestinal obstruction in an adult patient with successful laparoscopic management. We conclude that laparoscopic resolution is feasible, reproducible and may ensure a faster recovery in a selected group of patients.